Pengaruh Strategi Pemasaran Melalui Website Dan Personal Selling Terhadap Keputusan Pembelian PT. Wita Sukses Abadi - Rangga Rizqy Dhuha; Ade Rachmawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study is to examine the effect of Website-Based Marketing and Personal selling, both partially and simultaneously, on Purchase Decisions at PT Wita Sukses Abadi. This research employs a quantitative method with the population consisting of consumers of PT Wita Sukses Abadi and a sample of 89 respondents, determined using the saturated sampling technique. Data were collected through questionnaires, while the data analysis techniques included validity testing, reliability testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing, conducted with the assistance of SPSS version 31. The results show that Website-Based Marketing has a positive and significant partial effect on Purchase Decisions, with the regression equation Y = 10.838 + 0.391X1, a correlation coefficient of 0.804, and a coefficient of determination of 64.7%, while the t-test results indicate t count of 12.623 > t table of 1.988 with a significance value of 0.000 < 0.05, meaning that Ha₁ is accepted and H₀₁ is rejected. Furthermore, Personal selling also has a positive and significant partial effect on Purchase Decisions, with the regression equation Y = 0.628 + 0.974X2, a correlation coefficient of 0.950, and a coefficient of determination of 90.3%, while the t-test results show t count of 28.444 > t table of 1.988 with a significance value of 0.000 < 0.05, indicating that Ha₂ is accepted and H₀₂ is rejected. Simultaneously, Website-Based Marketing and Personal selling have a positive and significant effect on Purchase Decisions, with the regression equation Y = 0.650 + 0.069X1 + 0.859X2, a correlation coefficient of 0.954, and a coefficient of determination of 91.0%, while the F-test results indicate F count of 436.762 > F table of 3.103 with a significance value of 0.000 < 0.05, meaning that Ha₃ is accepted and H₀₃ is rejected.